Functional Movement Assessments Are Not Associated with Risk of Injury During Military Basic Training. Issue 11 (24th May 2019) - de la Motte, Sarah J; Clifton, Daniel R; Gribbin, Timothy C; Beutler, Anthony I; Deuster, Patricia A
Abstract: Introduction: Musculoskeletal injuries (MSK-I) in the U.S. military accounted for more than four million medical encounters in 2017. The Military Entrance Processing Screen to Assess Risk of Training (MEPSTART) was created to identify MSK-I risk during the first 180 days of military service. Methods: Active duty applicants to the United States Army, Navy, Air Force, and Marine Corps between February 2013 and December 2014 who consented completed a behavioral and injury history questionnaire and the MEPSTART screen [Functional Movement Screen (FMS), Y-Balance Test (YBT), Landing Error Scoring System (LESS), and Overhead Squat assessment (OHS)] the day they shipped to basic training. Male ( n = 1, 433) and Female ( n = 281) applicants were enrolled and MSK-I were tracked for 180 days. Binomial logistic regression and multivariate Cox proportional hazards modeling were used to assess relationships among MEPSTART screens and MSK-I independent of age, BMI, sex, Service, injury history, and smoking status. Analyses were finalized and performed in 2017. Results: The only functional screen related to injury was the LESS score. Compared to those with good LESS scores, applicants with poor LESS scores had lower odds of MSK-I (OR = 0.54, 95% CI = 0.30–0.97, p = 0.04), and a lower instantaneous risk of MSK-I during the first 180 d (HR = 0.58, 95%CI = 0.34–0.96, p = 0.04). However, secondary receiver operator characteristic (ROC) analyses revealed poor discriminative value (AUC = 0.49, 95%CI = 0.43–0.54). Conclusions: Functional performance did not predict future injury risk during the first 180 days of service. Poor LESS scores were associated with lower injury risk, but ROC analyses revealed little predictive value and limited clinical usefulness. Comprehensive risk reduction strategies may be preferable for mitigating MSK-I in military training populations.